Unraveling the impact of lanthanum on methane consuming microbial communities in rice field soils - Liu, Ruyan; Wei, Ziting; Dong, Wanying; Wang, Rui; Adams, Jonathan M.; Yang, Lin; Krause, Sascha M. B. (Frontiers in Microbiology, 2024)
The discovery of the lanthanide requiring enzymes in microbes was a significant scientific discovery that opened a whole new avenue of biotechnological research of this important group of metals. However, the ecological impact of lanthanides on microbial communities utilizing methane (CH4) remains largely unexplored. In this study, a laboratory microcosm model experiment was performed using rice field soils with different pH origins (5.76, 7.2, and 8.36) and different concentrations of La 3+ in the form of lanthanum chloride (LaCl3). Results clearly showed that CH4 consumption was inhibited by the addition of La 3+ but that the response depended on the soil origin and pH. 16S rRNA gene sequencing revealed the genus Methylobacter, Methylosarcina, and Methylocystis as key players in CH4 consumption under La 3+ addition. We suggest that the soil microbiome involved in CH4 consumption can generally tolerate addition of high concentrations of La 3+ , and adjustments in community composition ensured ecosystem functionality over time. As La 3+ concentrations increase, the way that the soil microbiome reacts may not only differ within the same environment but also vary when comparing different environments, underscoring the need for further research into this subject.